2002
DOI: 10.1074/jbc.m112107200
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-dependent Protein Kinase Types I and II Differentially Regulate cAMP Response Element-mediated Gene Expression

Abstract: We have shown that ethanol induces translocation of cAMP-dependent protein kinase (PKA) to the nucleus, cAMP response element-binding protein (CREB) phosphorylation, and cAMP response element-mediated gene transcription in NG108-15 cells. However, little is known about which PKA types regulate this process. We show here that under basal conditions NG108-15 cells contain type I PKA (C␤RI␤) primarily in cytosol and type II PKA (C␣RII␤) in the particulate and nuclear fractions. Antagonists of both type I and type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 49 publications
3
35
1
Order By: Relevance
“…Distinctive responses of the two types of PKA to ethanol treatment were seen in cultured neuroblastoma-Xglioma cells by Constantinescu et al (2002), who found that type II PKA is translocated to the nucleus to phosphorylate CREB, whereas type I remains in the cytoplasm to activate other transcription cofactors that then interact with phosphorylated CREB. In Aplysia sensory neurons, the functions of the two types of R differ primarily because of the polarity of neurons, type I PKA operating in the cell body and type II at nerve terminals.…”
Section: The Action Of the Two Pkas Is Complementarymentioning
confidence: 99%
“…Distinctive responses of the two types of PKA to ethanol treatment were seen in cultured neuroblastoma-Xglioma cells by Constantinescu et al (2002), who found that type II PKA is translocated to the nucleus to phosphorylate CREB, whereas type I remains in the cytoplasm to activate other transcription cofactors that then interact with phosphorylated CREB. In Aplysia sensory neurons, the functions of the two types of R differ primarily because of the polarity of neurons, type I PKA operating in the cell body and type II at nerve terminals.…”
Section: The Action Of the Two Pkas Is Complementarymentioning
confidence: 99%
“…Translocation and activation of RII-, but not RI-, PKA induces CREB phosphorylation that is necessary but insufficient for gene transcription (Constantinescu et al, 2002), whereas downregulation of RII␤-PKA by antisense oligonucleotides inhibits cAMP-induced nuclear signaling and CREB phosphorylation (Paolillo et al, 1999). Furthermore, anchoring by AKAP150 increases the rate, magnitude, and sensitivity of PKA signaling to the nucleus, increasing by 10-fold both CREB phosphorylation and CRE-mediated gene transcription (Feliciello et al, 1997).…”
Section: Rii-pka and Visual Cortical Plasticitymentioning
confidence: 99%
“…The different exposure paradigms (IP injection vs. long-term self administration and withdrawal), rodent strain or cell-type selectivity may explain these differences. Acute ethanol can activate adenylate cyclase, which can activate CREB through PKA (Asher et al, 2002;Constantinescu et al, 2002). Chronic exposure leads to compensatory up-regulation of NMDA receptors, with withdrawal producing Ca 2+ -dependent hyper-excitibility (Hoffman and Tabakoff, 1994).…”
Section: Effects Of Etoh On Bdnf Signalingmentioning
confidence: 99%